Effect of Traditional Preparation Processing on the Total Phenol Content and Antioxidant Activity of Fallopia multiflora Thunb. - Thi Thuong, Bui; Xuan Sinh, Pham; Thanh Hai, Nguyen; Thi Thanh Binh, Nguyen; Xuan Tung, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2020)
This study evaluates the effects of traditional preparation on the total phenol content and in vitro antioxidant activity of Fallopia multiflora Thunb.. The experimental results show that the total phenol content calculated with gallic acid (GAE) of Fallopia multiflora Thunb. increased during preparation processing. The Fallopia multiflora Thunb. after preparation had a total phenol content of 22.73 ± 0.21 mg GAE/g, about 3% higher than the raw sample (22.03 ± 0.40 mg GAE/g). The preparation processing also significantly increased the antioxidant activity of Fallopia multiflora Thunb.. The concentration of extract, which could neutralize 50% of the free radicals generated from 2.2-diphenyl-1-picrylhydrazyl of medicinal materials, after processing was 53.71 ± 0.44 µg/ml, about 2.3 times lower when compared to raw pharmaceutical materials (124,38 ± 0,56 µg/ml). Keywords Fallopia multilflora Thunb., processing, antioxidant, total phenol, neutralized free radicals. References [1] P.X. Sinh, Traditional pharmacology, Medical Publishing House, Ha Noi, 2014, pp. 352-353 (in Vietnamese). [2] L. Lin, C. Qu, J. Ni, A novel method to analyze hepatotoxic components in Polygonum multiflorum using ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry, Journal of hazardous materials 299 (2015) 249-259. https://doi.org/10.1016/j.jhazmat.2015.06.014 [3] Y. Liu, Q. Wang, J. Yang, X. Guo, W. Liu, S. Ma, S. Li, Polygonum multiflorum Thunb.: a review on chemical analysis, processing mechanism, quality evaluation, and hepatotoxicity, Frontiers in pharmacology 9 (2018) 364. http://doi.org/10.3389 / fphar.2018.00364. [4] J. Huang, J.P. Zhang, J.Q. Bai, M.J. Wei, J. Zhang, Z.H. Huang, G.H. Qu, W. Xu, X.H. Qiu, Chemical profiles and metabolite study of raw and processed Polygoni Multiflori Radix in rats by UPLC-LTQ-Orbitrap MSn spectrometry, Chinese journal of natural medicines 16 (5) (2018) 375-400. http://doi.org/10.1016 / S1875-5364 (18) 30070-0. [5] L. Liang, J. Xu, W.W. Zhou, E. Brand, H.B. Chen, Z.Z. Zhao, Integrating targeted and untargeted metabolomics to investigate the processing chemistry of Polygoni Multiflori Radix, Frontiers in pharmacology 9 (2018) 934. http://doi.org/10.3389/fphar.2018.00934. [6] Ministry of Health, Vietnamese Pharmacopoeia V, Medical Publishing House, Ha Noi, part 2, 2018, pp 1180-1181 (in Vietnamese). [7] N.T.H. Ly, T.T. Thao, P.V. Truong, P.T. Thuong, Quality Evaluation of Fallopia multiflora in Vietnam Based on HPLC-FLD and Chemometrics, Natural Products Chemistry & Research 6(6) (2018) 1-7. http://doi.org/10.4172/2329-6836.1000346. [8] L. Lin, B. Ni, H. Lin, M. Zhang, X. Li, Xi. Yin, C. Qu, J. Ni, Traditional usages, botany, phytochemistry, pharmacology and toxicology of Polygonum multiflorum Thunb.: a review, Journal of Ethnopharmacology 159 (2015) 158-183. https://doi.org/10.1016/j.jep.2014.11.009. [9] G.A. Bounda, Y.U. Feng, Review of clinical studies of Polygonum multiflorum Thunb. and its isolated bioactive compounds, Pharmacognosy research 7 (3) (2015) 225. http://doi.org/10.4103 / 0974-8490.157957. [10] M.P. Kähkönen, A.I. Hopia, H.J. Vuorela, J.P. Rauha, K. Pihlaja, T. S. Kujala, M.Heinonen, Antioxidant activity of plant extracts containing phenolic compounds, Journal of agricultural and food chemistry 47 (10) (1999) 3954-3962. http://doi.org/10.1021 / jf990146l. [11] H.H. Lin, A. L. Charles, C.W. Hsieh, Y. ChiLee, J.Y. Ciou, Antioxidant effects of 14 Chinese traditional medicinal herbs against human low-density lipoprotein oxidation, Journal of traditional and complementary medicine 5 (1) (2015) 51-55. https://doi.org/10.1016/j.jtcme.2014.10.001.